2019
DOI: 10.3389/fimmu.2019.02758
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Metal Hypersensitivity in Total Knee Arthroplasty: A Case Report

Abstract: Delayed type hypersensitivity (DTH) reactions are considered infrequent complications in arthroplasty, but have been recognized to be associated with devastating morbidity and substantial decrease in quality of life of affected patients. Chronic inflammation of artificial joints and associated loss of peri-implant bone often require revision surgery. Methods for the diagnosis of implant-related DTH are available but infrequently considered to the full extent. Sequential diagnostics based on exclusion of septic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Damage to the cartilage on the joint surface can easily lead to osteoarthritis, and it is extremely difficult to regenerate the joint surface with vitreous cartilage again. For knee joints, metal prostheses have been clinically applied due to their durability; however, the risks of infection, metal allergy, and other problems have not yet been solved [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Damage to the cartilage on the joint surface can easily lead to osteoarthritis, and it is extremely difficult to regenerate the joint surface with vitreous cartilage again. For knee joints, metal prostheses have been clinically applied due to their durability; however, the risks of infection, metal allergy, and other problems have not yet been solved [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, this is the most common modality with which patients with metal hypersensitivity will be imaged, at least initially. Unfortunately, radiographic findings of metal hypersensitivity on radiographs are nonspecific, and the spectrum can range from synovial thickening, effusion, subcutaneous edema, to aseptic loosening seen as lucency around the implants 9 . These findings may share important overlap with those of an indolent infection or particle disease and thus may be difficult to differentiate.…”
Section: Radiology Physician Perspectivementioning
confidence: 99%
“…Ni is the most intensively studied metal allergen in vitro. Proliferation-based approaches, e.g., lymphocyte transformation or proliferation tests (LTT or LPT), Memory Lymphocyte Immunostimulation Assay (MELISA), or cytokine-secretion assays (e.g., Enzymelinked-immuno-Spot Assay (ELISpot)) have been employed [6,175]. Our group recently showed that CD154 upregulation identifies the Ni-specific CD4+ naïve and memory T cell pool in a fast, comprehensive and quantitative manner [115].…”
Section: Challenges Associated With Diagnostic In Vitro Testsmentioning
confidence: 99%
“…In summary, only some allergic individuals top background frequencies of metalspecific effector or memory T cells in blood-based in vitro tests (Figure 2). Further research is required to identify more distinctive, allergy-associated T cell subpopulations or, if tissue samples are available, in situ allergy-associated immune responses [175,190].…”
Section: Challenges Associated With Diagnostic In Vitro Testsmentioning
confidence: 99%